STRATEGI PENINGKATAN KUALITAS KOMUNIKASI PUBLIK DI LEVEL PEMERINTAHAN DESA - Ahmad Salman Farid (Jurnal Inovasi Penelitian, 2020)
This study aims to analyze the extent to which the quality of public communication provided by the village administration to the community and to form a strategy to improve the quality of public communication at the village government level. This research method uses qualitative-descriptive method which draws resources directly from several villages in Mandailing Natal Regency. The results of the study prove that there are still many shortcomings and weaknesses of public communication at the village government level and there is no awareness of improving the quality of communication. There are 8 strategies that researchers suggest including improving the quality of human resources in the field of communication and information, strengthening the integration of information governance and public communication in accordance with the principles of public information disclosure, strengthening local and alternative media as the main source of public information, need to provide public information content quality and equitable, especially for people in disadvantaged areas, an increase in access to public participation in determining public policies directly and digitally, increasing public media literacy through education and socio-cultural approaches, compiling village public relations standards and forming digital volunteers and strengthening the role of community leaders.